The DESIGN AND CONSTRUCTION OF ROBOTIC ARM ON AUTOMATIC MIG WELDING ROBOT - Ilham Rizqianto; Dedy Pradigdo; Ismanto Setyabudi (Jurnal Otoranpur, 2021)
Abstract: Tehnlogical advances to date have grown increasingly sophisticated technolgy, especially in robotic technogy which is currently developed to achieve work result that are make human work easier welding process with manual systems need to be switched to automatic systems. The mechanical concept of the arm that will be applied to Automatic Welding Carrier Machine by applying the mechanical concept of a 3D machine which is expected to increase mobility, working range of the tool as well as increasing the quality of automatic welding results. In this research, the method used is experimental research methods and simulations that aim to know the results of the analysis on the mechanics of the robot arm. The data generated after performing calculations with provide a load on the leadscrew of the compressive stress that occurs i the leadscrew is , the voltage bending is and the shear stress that occurs is , so that the lead crew is said to be able to encourge maximum allowable amount of . The torque required by the motor drive to push the received load on the Z ( ) axis is equal to , then the selection of the nema23 stepper motor is stated very capable as a robotic arm mover because have torque . With the loading of the 2020 profile arm rod at using ansys simulation, the maximum total deformation that may occur is , so that the 2020 profile rod can be said to be safe for use on Automatic Welding Carrier Machine.